ΔNp63 silencing, DNA methylation shifts, and epithelial-mesenchymal transition resulted from TAp63 genome editing in squamous cell carcinoma - Iyoko Katoh; Keiichi Tsukinoki; Ryu-Ichiro Hata; Shun-ichi Kurata (Neoplasia: An International Journal for Oncology Research, 2023)
TP63 (p63) is strongly expressed in lower-grade carcinomas of the head and neck, skin, breast, and urothelium to maintain a well-differentiated phenotype. TP63 has two transcription start sites at exons 1 and 3′ that produce TAp63 and ΔNp63 isoforms, respectively. The major protein, ΔNp63α, epigenetically activates genes essential for epidermal/craniofacial differentiation, including ΔNp63 itself. To examine the specific role of weakly expressed TAp63, we disrupted exon 1 using CRISPR-Cas9 homology-directed repair in a head and neck squamous cell carcinoma (SCC) line. Surprisingly, TAp63 knockout cells having either monoallelic GFP cassette insertion paired with a frameshift deletion allele or biallelic GFP cassette insertion exhibited ΔNp63 silencing. Loss of keratinocyte-specific gene expression, switching of intermediate filament genes from KRT(s) to VIM, and suppression of cell-cell and cell-matrix adhesion components indicated the core events of epithelial-mesenchymal transition. Many of the positively and negatively affected genes, including ΔNp63, displayed local DNA methylation changes. Furthermore, ΔNp63 expression was partially rescued by transfection of the TAp63 knockout cells with TAp63α and application of DNA methyltransferase inhibitor zebularine. These results suggest that TAp63, a minor part of the TP63 gene, may be involved in the auto-activation mechanism of ΔNp63 by which the keratinocyte-specific epigenome is maintained in SCC.